Jurisdiction of maternity and extension to the working father: some sentences of the Constitutional Court of Colombia - Figuera Vargas, Sorily Carolina (2019)
This article analyzes the problem that revolves around the jurisdiction of maternity and its extension to the working father within the geographical context of Colombia, from the year 2013 to the year 2018. The methodology of a jurisprudential investigation is used here, which examines the repercussion and meaning of judicial decisions as a useful tool for justice operators. This is a study focused on respect for human rights, the gender perspective and access to justice. One of the main results presented here is the evolution of jurisprudence in Colombia regarding the institution of the jurisdiction of maternity and its extension to the working father. It was concluded then that in this legal system, an articulation of the aforementioned rights was achieved, with other constitutional prerogatives such as the protection of the family unit; as well as, the best interests of boys and girls. The scope of this analysis is typical of the study of a foreign legal system, with the intention of examining its avant-garde precepts.